Friction and Wear characteristics of CF/PEEK against 431 stainless steel under high hydrostatic pressure water lubrication. (November 2020) - Guan, Ziwei; Wu, Defa; Cheng, Qian; Wang, Zhenyao; Tang, Meilihua; Liu, Yinshui
Abstract: The influence of high hydrostatic pressure on tribological characteristics of carbon fiber reinforced Poly-ether-ether-ketone (CF/PEEK) against 431 stainless steel (431SS) was investigated. Hydrostatic pressure ranged from normal pressure to 80 MPa at a step of 20 MPa to simulate the environmental pressure of the deep ocean. The results suggest that the average friction coefficient decreases with increased hydrostatic pressure. Hydrostatic pressure helps reduce the wear rates of CF/PEEK and 431SS. As the pressure increases, the main wear and friction mechanism of CF/PEEK changes from adhesive wear to fatigue wear, while the main wear mechanism of 431SS is abrasive wear. Compared with the sliding surface after normal pressure experiments, the surface roughness Ra of CF/PEEK will be smaller after high pressure experiments. The crystallinity of CF/PEEK decreases linearly with hydrostatic pressure, indicating a possible decline in mechanical properties. Moreover, comprehensive results suggest that this friction pair can be used under the hydrostatic pressure up to 80 MPa. Graphical abstract: Unlabelled Image Highlights: Hydrostatic pressure ranges from normal pressure to 80 MPa at a step of 20 MPa. Increased hydrostatic pressure helps reduce the friction coefficient and the wear rates of CF/PEEK and 431SS. As the pressure increases, the main wear and friction mechanism of CF/PEEK changes from adhesive wear to fatigue wear. The main wear mechanism of 431SS is abrasive wear. The crystallinity of CF/PEEK decreases almost linearly with hydrostatic pressure.